Model Eksponensial dan Logistik pada Pertumbuhan Penduduk di Kota Tomohon - Lenak, Lorenza Raquel; Pascoal, Richard Gland; Layuk, Jelita Milka Tirza; Arunde, Prida; Kenap, Wilka Michael; Silaban, Afia Rebeka; Katampuge, Widiawaty; Mangobi, James U. L.; Maukar, Marvel Grace (Jurnal Ilmiah Wahana Pendidikan, 2026)
Population growth that continues to increase will have a positive and negative impact. To anticipate the occurrence of negative impacts, we have to make forecasts about population growth. This study aims to forecast population growth in Tomohon City using differential equations called Exponential Model of Population Growth and Logistic Model of Population Growth. In this study, the authors used population data from the Central Bureau of Statistics in Tomohon City. The authors took data in 2015-2024. The results showed that the most appropriate exponential model to forecast the number of population is a model with k = 0.00297402 and the forecast number of population in Tomohon City in 2025 is 104.121 people. Meanwhile, the most appropriate logistic model to forecast the number of population is a model with r = 0.05283328 and the forecast number of population in Tomohon City in 2025 (t = 10) is 104,113 people